Recovery of residual polyamide (PA12) from polymer powder bed fusion additive manufacturing process through a binder jetting process - Balderrama Armendariz, Cesar Omar (2024)
Purpose This study aims to propose the reuse of PA12 (powder) in another AM process, binder jettiinng, which is less sensitive to the chemical and mechanical degradation of the powder after multiple cycles in the laser system.